Financial reporting risk and business risk assessments as fraud detection mechanism and its impact on audit pricing / Wan Mardyatul Miza Wan Tahir and Dr Halil Paino - Wan Tahir, Wan Mardyatul Miza; Paino, Halil (Research Management Institute (RMI), 2012)
Financial information that has being deteriorated by fraud will misled users. Hence, the main objective of this paper is to identify the association between five ratios of financial reporting risks to predict fraud. Furthermore, this paper also investigates the impacts of fraud detection on audit fee. Thus, sample of 10 of fraudulent companies and sample of 40 non fraudulent companies are being identified to achieve the objective. Stepwise logistic regression was being employed. The results clearly indicate that changes in sales, receivables and allowance for doubtful debts have significant effect of fraud detection. However, fraud detection gives no or little impact on audit fees.